Attitudes about dental care among parents whose children suffer from severe congenital heart disease: a case-control study - K. GRAHN, S. WIKSTRÖM, L. NYMAN, A. RYDBERG, & C. STECKSÉN-BLICKS (Paediatric Dentistry, 2006)
To examine attitudes and experiences of parents whose children have complex congenital heart disease (CHD) with respect to dental health information and advice, dental care, and service and to compare the results with data from an age- and gender-matched control group without any medical problems.